Camellia sinensis (L.) Kuntze Extract Attenuates Ovalbumin-Induced Allergic Asthma by Regulating Airway Inflammation and Mucus Hypersecretion - Sohi Kang; Hyun-Yong Kim; A Yeong Lee; Hyo Seon Kim; Jun Hong Park; Byeong Cheol Moon; Hyeon Hwa Nam; Sung-Wook Chae; Bokyung Jung; Changjong Moon; In Sik Shin; Joong Sun Kim; et al. (Pharmaceutics, 2023)
Asthma is a pulmonary disease induced by the inhalation of aeroallergens and subsequent inappropriate immune responses. Camellia sinensis (L.) Kuntze has been evaluated as an effective antioxidant supplement produced from bioactive compounds, including flavonoids. In this study, we aimed to determine the effects of Camellia sinensis (L.) Kuntze extract (CE) on ovalbumin-induced allergic asthma. The components of CE were analyzed using high-performance liquid chromatography (HPLC) chromatogram patterns, and asthmatic animal models were induced via ovalbumin treatment. The antioxidant and anti-inflammatory effects of CE were evaluated using 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS), and nitric oxide (NO) assays. Seven compounds were detected in the CE chromatogram. In the ovalbumin-induced mouse model, CE treatment significantly decreased the inflammation index in the lung tissue. CE also significantly decreased eosinophilia and the production of inflammatory cytokines and OVA-specific IgE in animals with asthma. Collectively, our results indicate that CE has anti-inflammatory and antioxidant activities, and that CE treatment suppresses asthmatic progression, including mucin accumulation, inflammation, and OVA-specific IgE production.